Genetic association between milk yield, stayability, and mastitis in Holstein cows under tropical conditions - Irano, Natalia [UNESP]; Bignardi, Annaiza Braga [UNESP]; El Faro, Lenira; Santana, Mario Luiz; Cardoso, Vera Lucia; Albuquerque, Lucia Galvao [UNESP] (Springer, 2014)
The objective of this study was to estimate genetic parameters for milk yield, stayability, and the occurrence of clinical mastitis in Holstein cows, as well as studying the genetic relationship between them, in order to provide subsidies for the genetic evaluation of these traits. Records from 5,090 Holstein cows with calving varying from 1991 to 2010, were used in the analysis. Two standard multivariate analyses were carried out, one containing the trait of accumulated 305-day milk yields in the first lactation (MY1), stayability (STAY) until the third lactation, and clinical mastitis CM), as well as the other traits, considering accumulated 305-day milk yields Y305), STAY, and CM, including the first three lactations as repeated measures for Y305 and CM. The co-variance components were obtained by a Bayesian approach. The heritability estimates obtained by multivariate analysis with MY1 were 0.19, 0.28, and 0.13 for MY1, STAY, and CM, respectively, whereas using the multivariate analysis with the Y305, the estimates were 0.19, 0.31, and 0.14, respectively. The genetic correlations between MY1 and STAY, MY1 and CM, and STAY and CM, respectively, were 0.38, 0.12, and -0.49. The genetic correlations between Y305 and STAY, Y305 and CM, and STAY and CM, respectively, were 0.66, -0.25, and -0.52.
Keywords: Genetic correlation; Heritability; repeatability; Selection